BATASAN PENGGUNAAN HAK PILIH BAGI APARATUR SIPIL NEGARA DALAM PEMILU DAN PEMILIHAN TAHUN 2024 - Rahmawati, Tri; Latif, Udin (Muadalah : Jurnal Hukum, 2024)
This article discusses the use of voting rights for State Civil Apparatus Employees in Elections and Elections. The 1945 Constitution of the Republic of Indonesia and Law Number 39 of 1999 concerning Human Rights have guaranteed the political right of citizens to vote and be elected, which is essentially the right of every citizen. The findings from the results of this study show that Law Number 20 of 2023 concerning the State Civil Apparatus, in which an action plan has been designed by building clean, effective, democratic, and reliable governance. To make it happen, ASN is needed as the main bureaucratic engine that is professional, neutral and free from political intervention, corruption and practices, collusion, nepotism, and carries out its role as the glue of national unity and unity based on Pancasila and the 1945 Constitution of the Republic of Indonesia.